América Latina: Estado e reformas numa perspectiva comparada - Castro, Alda Maria Duarte Araújo (Revista Educação em Questão, 2006)
KRAWCZYK, Nora Rut; WANDERLEY, Luiz Eduardo. (Org.). América Latina: Estado e reformas numa perspectiva comparada. São Paulo: Cortez, 2003.